Transplant: a non-fiction narrative. Issue 1 (1st June 2002) - Rowe, M
Abstract : This narrative is taken from a memoir about my son, Jesse, who died at age 19 in 1995 after a liver transplant. It covers two periods—from May 5, his admission date at the hospital to wait for a transplant, until May 9, when a perforation, caused by cutting through intestinal adhesions during transplant surgery, was discovered, and from May 20 to May 22, when his condition became extremely critical. Since Jesse was largely unconscious or semi-conscious during a good part of the period this narrative covers, his personality and conscious struggles shine through less here than they do in other parts of the memoir. Here, the relative emphasis is on parents and physicians and on facing the critical illness, and possible death, of one's child in an intensive care unit, following the very intervention that was to give him a new chance at a healthy life.